HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKN DENGAN MODEL SNOWBALL THROWING DIKELAS V SDN - Vani, Desri; Reinita, Reinita; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at improving student’s learning outcomes of Cicics subject. It was conducted at SDN 07 Batang Kapas, Pesisir Selatan. This class action research applied both qualititative and quantitative apporaches. The subjects were the teacher and 22 students of Class V. The research result shows that the plannig phase, implementation phase, and student’s learrning outcomes have have successfully improved. Thus, it can be concluded that the Snowball Throwing Model improves student’s learning outcomes of Civics subject.